A Phylogenetic Study of the ANT Family Points to a preANT Gene as the Ancestor of Basal and euANT Transcription Factors in Land Plants - Dipp-Álvarez, Melissa; Cruz-Ramírez, Alfredo (Frontiers in Plant Science, 2019)
Comparative genomics has revealed that members of early divergent lineages of land plants share a set of highly conserved transcription factors with flowering plants. While gene copy numbers have expanded through time, it has been predicted that diversification, co-option, and reassembly of gene regulatory networks implicated in development are directly related to morphological innovations that led to more complex land plant bodies. Examples of key networks have been deeply studied in Arabidopsis thaliana, such as those involving the AINTEGUMENTA (ANT) gene family that encodes AP2-type transcription factors (TFs). These transcription factors play significant roles in plant development such as the maintenance of stem cell niches, the correct development of the embryo and the formation of lateral organs, as well as fatty acid metabolism. Previously, it has been hypothesized that the common ancestor of mosses and vascular plants encoded two ANT genes that later diversified in seed plants. However, algae and bryophyte sequences have been underrepresented from such phylogenetic analyses. To understand the evolution of ANT in a complete manner, we performed phylogenetic analyses of ANT protein sequences of representative species from across the Streptophyta clade, including algae, liverworts, and hornworts, previously unrepresented. Moreover, protein domain architecture, selection analyses, and regulatory Cis elements prediction, allowed us to propose a scenario of how the evolution of ANT genes occurred. In this study we show that a duplication of a preANT-like gene in the ancestor of embryophytes may have given rise to the land plant-exclusive basalANT and euANT lineages. We hypothesize that the absence of euANT-type and basalANT-type sequences in algae, and its presence in extant land plant species, suggests that the divergence of pre-ANT into basal and eu-ANT clades in embryophytes may have influenced the conquest of land by plants, as ANT TFs play important roles in tolerance to desiccation and the establishment, maintenance, and development of complex multicellular structures which either became more complex or appeared in land plants.